Trefoil‐Shaped Porous Nanographenes Bearing a Tribenzotriquinacene Core by Three‐fold Scholl Macrocyclization. Issue 41 (17th September 2018) - He, Lisi; Ng, Chun‐Fai; Li, Yuke; Liu, Zhifeng; Kuck, Dietmar; Chow, Hak‐Fun
Abstract: Porous curved polycyclic aromatic compounds6 and14 bearing a tribenzotriquinacene (TBTQ) core encircled by an m, p, p, m, m, p, p, m, m, p, p, m ‐cyclododecaphenylene belt were synthesized and characterized by NMR spectroscopy and mass spectrometry. These trefoil hydrocarbon macrocycles were constructed in high yield using an intramolecular three‐fold Scholl macrocyclization. X‐ray crystal analysis of14 demonstrated a large wizard‐hat‐shaped structure with three pores (radii 2.9–3.0 Å). The π‐stacking aggregation of the hexa‐ n ‐dodecyloxy derivative6 a and the chloride anion binding properties of14 were studied by NMR spectroscopy. Such stacking and anion binding properties were much weaker in the singly11 and doubly macrocyclized products12 . Abstract : Sorting hat : Trefoil‐shaped porous curved nanographenes bearing a tribenzotriquinacene (TBTQ) core encircled by an m, p, p, m, m, p, p, m, m, p, p, m ‐cyclododecaphenylene belt were synthesized in good yields through a non‐classical three‐fold Scholl macrocyclization.